1970
DOI: 10.1088/0022-3727/3/6/307
|View full text |Cite
|
Sign up to set email alerts
|

The stylus or scratch method for thin film adhesion measurement: some observations and comments

Abstract: The effect of applying a rounded stylus to thin metallic films on glass substrates has been investigated using diamond and steel styli with tip radii of approximately 25 μm and loadings of up to 230 g. The films were vacuum-deposited indium, tin, lead, gold, copper, aluminium, nickel, chromium and molybdenum of various thicknesses up to 3·2 μm. Scanning electron microscope and optical interference microscope observations showed that the process of scratch formation was generally very complex and varied with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…Chopra [10] found that the critical load increases linearly with increasing film thickness when film exceeds 200 nm in thickness. Butler et al [11] have shown that the fundamental processes involved in the Scratch Test are very complex and that it is not possible to deduce film adhesion by the simple static model as proposed by Benjamin and Weaver. Oroshnik and Croll [12] used a sensitive scratch tester and found that each stylus exhibited its own testing characteristics.…”
Section: Existing Methods For Adhesion Measurementmentioning
confidence: 99%
“…Chopra [10] found that the critical load increases linearly with increasing film thickness when film exceeds 200 nm in thickness. Butler et al [11] have shown that the fundamental processes involved in the Scratch Test are very complex and that it is not possible to deduce film adhesion by the simple static model as proposed by Benjamin and Weaver. Oroshnik and Croll [12] used a sensitive scratch tester and found that each stylus exhibited its own testing characteristics.…”
Section: Existing Methods For Adhesion Measurementmentioning
confidence: 99%
“…Figure 10 is an electron micrograph of the scratch produced which shows film becoming detached and forming a small hillock or bubble ahead of the stylus and some detachment and raising of the film on either side of the actual track. 70 Very recently, Weaver 0 has analysed the behavior depicted in Figure 10, and his theoretical analysis, apparently, offers explanation for all the observable details in the micrograph. Moreover, it modifies and expands the details of how the film is removed, but the initial state is still dependent upon the shearing force under the stylus.…”
Section: Mechanical Methodsmentioning
confidence: 99%
“…When a critical load was reached, this shearing force was equal to the interfacial shear strength and thus complete removal of the film from the substrate occurred. However, Butler et al [3] observed that the process of scratch formation was very complex and concluded that no absolute values of adhesion could be deduced. Further studies also showed the limitation of the simple model described by Benjamin and Weaver [4][5][6][7].…”
Section: Theorymentioning
confidence: 99%